Peningkatan Daya Saing UMKM Ceriping Singkong di Desa Blorong Kecamatan Jumantono Karanganyar melalui Jejaring Kerja dan Kolaborasi antar UMKM - Wibowo, Edi; Ola, Damas Ivan (Institut Ilmu Sosial dan Manajemen Stiami, 2025)
The majority of the people of Blorong Village make their living as farmers, this is supported by the geographical condition of the village which has many rice fields with easily accessible rivers. There are several people in Blorong Village who are developing home-based businesses, one of which is the Ceriping Singkokng business. The raw material potential in Blorong Village has a lot of cassava which is processed into chips. The demand for cassava chips has a high market demand. The workforce in Blorong Village has a lot of workers who are skilled at making cassava chips. Regional government support provides support to MSMEs, such as training and capital assistance. The problems that exist in these MSMEs include lack of networking and collaboration between MSMEs, limited access to information and knowledge about marketing and branding, tight competition with cassava chip products from other regions, inconsistent product quality. The impacts include, among others, the competitiveness of the cassava chip MSMEs in Blorong Village is still low, difficulties in penetrating a wider market, and the income of cassava chip MSMEs is still low. The results of this activity are able to increase the collaboration network between MSME actors so that it will increase the income and welfare of these MSME actors.